O princípio misericórdia. Uma contribuição à questão dos princípios em bioética - Martins, Rogério Jolins Jolins (Revista eclesiástica brasileira, 2008)
This study is about the principle of mercy formulated by Jon Sobrino in theology and put in the context of the principles in Bioethics. Mostly attributed to the North American principialism, bioethics hold marks from the liberalism reinforced by the Kantian principle of autonomy. The principle of mercy offers a crucial counterpoint which comes from the vulnerability of the poor and their social condition named by Sobrino as a “people of crucified ones”. Suppressing the formulation of a naïve mercy, its spiritual strength joins the demands of responsibility in order to be capable to change and to transform realities. So, the principle of mercy can reinforce the bioethical tendencies in Brazil in overlapping its circumscription to the principialism in the field of health relations, in order to reach a social bioethics with a broader inclusion of the poor.